Ifza Mechtech: Ifza Fold / Muhammad Zikry Aizat Moharam ...[et al.] - Moharam, Muhammad Zikry Aizat; Yusof, Muhammad Amirul Fiesal; Daud, Aimi Nabila; Fauzi, Ilyasa' Hakim (2019)
Folding clothes is one of the basic duties that we should have done almost every day. By folding clothes, we can train ourselves to be more discipline. It is because folding clothes take times to finish. For the person that really prioritize tidiness, this process can really help them as it can prevent the clothes from wrinkle. Folding clothes also can help to minimize the usage of space whether in a shop lot or in a house.